Uma introdução à álgebra de Lipschitz - Silva Neto, Manoel Felipe da (2021)
The aim of this work is to introduce a study about Lipschitz algebra. Initially, we will approach the bounded Lipschitz functions, Lipschitz functions which preserve the base point and Arens-Ells space. Next, we will study the class of the 2-Lipschitz operators, which can be seen as a natural extension of the continuous bilinear operators for the Lipschitz context, and we wil present a method to obtain 2-Lipschitz operator ideals from linear operator ideals. At last, we will give some examples of 2-Lipschitz operator ideals.